A General and Straightforward Route to Noble Metal‐Decorated Mesoporous Transition‐Metal Oxides with Enhanced Gas Sensing Performance. Issue 46 (24th September 2019) - Ma, Junhao; Xiao, Xingyu; Zou, Yidong; Ren, Yuan; Zhou, Xinran; Yang, Xuanyu; Cheng, Xiaowei; Deng, Yonghui
Abstract: Controllable and efficient synthesis of noble metal/transition‐metal oxide (TMO) composites with tailored nanostructures and precise components is essential for their application. Herein, a general mercaptosilane‐assisted one‐pot coassembly approach is developed to synthesize ordered mesoporous TMOs with agglomerated‐free noble metal nanoparticles, including Au/WO3, Au/TiO2, Au/NbO x, and Pt/WO3 . 3‐mercaptopropyl trimethoxysilane is applied as a bridge agent to cohydrolyze with metal oxide precursors by alkoxysilane moieties and interact with the noble metal source (e.g., HAuCl4 and H2 PtCl4 ) by mercapto (SH) groups, resulting in coassembly with poly(ethylene oxide)‐ b ‐polystyrene. The noble metal decorated TMO materials exhibit highly ordered mesoporous structure, large pore size (≈14–20 nm), high specific surface area (61–138 m 2 g −1 ), and highly dispersed noble metal (e.g., Au and Pt) nanoparticles. In the system of Au/WO3, in situ generated SiO2 incorporation not only enhances their thermal stability but also induces the formation of ε‐phase WO3 promoting gas sensing performance. Owning to its specific compositions and structure, the gas sensor based on Au/WO3 materials possess enhanced ethanol sensing performance with a good response ( R air / R gas = 36–50 ppm of ethanol), high selectivity, and excellent low‐concentration detection capability (down to 50 ppb) at low working temperature (200 °C). Abstract : A series of noble metal nanoparticles (Au/Pt NPs)‐decorated silica/transition metal oxide (WO3, TiO2, and NbO x ) hybrid materials are successfully synthesized via a mercaptosilane‐assisted straightforward coassembly strategy. The obtained hybrid materials possess highly ordered and stable mesoporous structures with highly dispersed noble metal NPs. The Au NPs–decorated SiO2 /WO3 materials show excellent ethanol sensing with high sensitivity and ultralow detection limits.